Writing Skills Development for Graduate Studies and Career Readiness in Science and Aging Fields: A Case Study Approach - McRell, Amanda Stafford; Wilson, Betty L.; Levkoff, Sue E. (Frontiers in Public Health, 2021)
Increasing the number of racially and ethnically underrepresented students who pursue scientific graduate studies in programs focusing on science and aging offers an opportunity to increase the number of aging specialists while simultaneously promoting diversity in the research labor market and supporting new ideas. This case study aims to better understand how students participating in an academic preparatory program experience a writing class contextualized within (1) students' writing background and (2) students' future ambitions related to science and aging. The individually-tailored writing class was taught as a critical component of a comprehensive educational program that targets underrepresented racial and ethnic minority undergraduate students who are interested in pursuing scientific graduate studies in fields related to aging. The researchers conducted semi-structured qualitative interviews with students (n = 4) enrolled in the 24-month fellowship training program, which included participation in the writing course during the summer prior to their senior year of undergraduate education. All participants were young adult college students who identified as Black or African American and female. Using thematic coding, statements about professional writing skills were divided into four primary themes: (1) prior experiences, (2) class experiences, (3) future goals and ambitions, and (4) structural considerations. These themes suggest potential implications for effective interventions aimed to advance the writing skills and academic and career readiness of racially and ethnically diverse students entering fields of science and aging.